A prototype of mobile info system portal web-based system / Rashidah Abd Aziz - Abd Aziz, Rashidah (2005)
Mobile Info System is a system where the subscriber will be informed via short message system (SMS). The subscriber will receive the latest information about what is happening at FTMSK and any other announcement or events through SMS to keep them updated and alert. The SMS push system will be implemented here. What I am going to do here is the subscription to the system. The student can subscribe to the system through the portal I made, "Subscription to hifo Mobile System and Student Portal" is a web-based system which has 2 sections. The first section is for students to view all the latest news about job vacancy, the latest technology and also the latest events that will be happening at FTMSK. They can post bulletin and there is a forum for them to discuss about anything. Besides that, they can update their profile and change their password. The second section is for the administrator's view, where he is the one who put the latest news and manage the students' profile, the bulletin board and the forum. Both sections are protected by using usemame and password.